Basal and Activated Calcium Sensitization Mediated by RhoA/Rho Kinase Pathway in Rats with Genetic and Salt Hypertension. (19th January 2017) - Behuliak, Michal; Bencze, Michal; Vaněčková, Ivana; Kuneš, Jaroslav; Zicha, Josef
Abstract : Calcium sensitization mediated by RhoA/Rho kinase pathway can be evaluated either in the absence (basal calcium sensitization) or in the presence of endogenous vasoconstrictor systems (activated calcium sensitization). Our aim was to compare basal and activated calcium sensitization in three forms of experimental hypertension with increased sympathetic tone and enhanced calcium entry—spontaneously hypertensive rats (SHR), heterozygous Ren-2 transgenic rats (TGR), and salt hypertensive Dahl rats. Activated calcium sensitization was determined as blood pressure reduction induced by acute administration of Rho kinase inhibitor fasudil in conscious rats with intact sympathetic nervous system (SNS) and renin-angiotensin system (RAS). Basal calcium sensitization was studied as fasudil-dependent difference in blood pressure response to calcium channel opener BAY K8644 in rats subjected to RAS and SNS blockade. Calcium sensitization was also estimated from reduced development of isolated artery contraction by Rho kinase inhibitor Y-27632. Activated calcium sensitization was enhanced in all three hypertensive models (due to the hyperactivity of vasoconstrictor systems). In contrast, basal calcium sensitization was reduced in SHR and TGR relative to their controls, whereas it was augmented in salt-sensitive Dahl rats relative to their salt-resistant controls. Similar differences in calcium sensitization were seen in femoral arteries of SHR and Dahl rats.